2011
DOI: 10.1111/j.1745-493x.2011.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Supplier Integration in the Chinese Automotive Industry: The Buyer's Perspective

Abstract: This paper presents the results of an empirical analysis of the current practices of, and key challenges to, domestic supplier integration in the Chinese automotive industry from the buyer's perspective. The results are based on case interviews with thirty automotive firms from various countries of origin with manufacturing operations in China. The research findings indicate that domestic supplier integration in terms of joint product development and advanced production planning activities between buyers and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 102 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…) within the organization (e.g., attempts by the rank and file to influence top management) and across organizations (e.g., collaborative relationships that foster multiorganizational initiatives (Lockström et al. ; Fawcett et al. ) and leveraging innovation with suppliers (Wagner ).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…) within the organization (e.g., attempts by the rank and file to influence top management) and across organizations (e.g., collaborative relationships that foster multiorganizational initiatives (Lockström et al. ; Fawcett et al. ) and leveraging innovation with suppliers (Wagner ).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The positive impact of supplier integration for firms worldwide has been shown in supply chain management literature (Petersen, Handfield, & Ragatz, 2005;Das, Narasimhan, & Talluri, 2006; Krause, Handfield, & Tyler, 2007;Paulraj & Chen, 2007;Terpend, Tyler, Krause, & Handfield, 2008;Azadegan & Dooley, 2010;Lockström, Schadel, Harrison, Moser, & Malhotra, 2010;Lockstrom, Schadel, Moser, & Harrison, 2011). However, as noted by Fawcett, Fawcett, Watson and Magnan (2012), different behavioral constraints that impede supplier collaboration can emerge from different institutional, cultural, and organizational contexts.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Lockstrom et al. () interviewed the purchasing manager, quality manager, or general manager of sampled companies and found that “there is a great deal of adversarial behavior where information asymmetry plays an important role, rendering full openness very difficult. This is reflected in the low degree of open book policies.”…”
Section: Introductionmentioning
confidence: 99%
“…The per‐unit cost of producing a garment of different colors may be the same, but the extra color could cost more. Because of information asymmetry (see, e.g., Lockstrom et al., and the references therein), the exact cost of producing an assortment is a closely guarded secret of many manufacturers. By following the previous literature in Marketing and Operations Management (e.g., Gaur & Honhon, ; Kurtulus & Nakkas, ), we assume that the cost of producing an assortment is linear with respect to the total quantity and the number of variants.…”
Section: Introductionmentioning
confidence: 99%